Fracture of Sn-Ag-Cu solder joints on Cu substrates : I. effects of loading and processing conditions - Pang, John Hock Lye (2013)
During service, microcracks form inside solder joints, making microelectronic packages highly prone to failure on dropping. Hence, the fracture behavior of solder joints under drop conditions at high strain rates and under mixed-mode conditions is a critically important design consideration for robust joints. This study reports on the effects of joint processing and loading conditions on the microstructure and fracture response of Sn-3.8%Ag-0.7%Cu (SAC387) solder joints attached to Cu substrates. The impact of parameters which control the microstructure (reflow condition, aging) as well as loading conditions (strain rate and loading angle) are explicitly studied. A methodology based on the calculation of the critical energy release rate, G C, using compact mixed-mode (CMM) samples was developed to quantify the fracture toughness of the joints under conditions of adhesive (i.e., interface-related) fracture. In general, higher strain rate and increased mode-mixity resulted in decreased G C. G C also decreased with increasing dwell time at reflow temperature, which produced a thicker intermetallic layer at the solder–substrate interface. Softer solders, produced by slower cooling following reflow, or post-reflow aging, showed enhanced G C. The sensitivity of the fracture toughness to all of the aforementioned parameters reduced with an increase in the mode-mixity. Fracture mechanisms, elucidating the effects of the loading conditions and process parameters, are briefly highlighted.